Reconsidering the costs of commitment: Learning and state acceptance of the UN human rights treaties' individual complaint procedures - Andreas Johannes Ullmann (The Review of International Organizations, 2024)
How do states react to adverse decisions resulting from human rights treaties' individual complaint procedures? While recent scholarship has shown particular interest in states' reactions to international court judgments, research on state behavior vis-à-vis an increasing treaty body output remains scarce. I argue that states generally want to avoid the costs implied by adverse decisions, or `views'. Rising numbers of rebukes lead them to update their beliefs about the costliness of complaint procedure acceptance in a Bayesian manner. As a result, states become less inclined to accept further petition mechanisms under different human rights treaties. I test these assumptions on an original dataset containing information on individual complaint procedure acceptance and the distribution of 1320 views for a total number of 169 countries ranging from the year 1965 to 2018. Results from Cox proportional hazards regressions suggest that both the number of views against neighboring states and against the examined state itself decrease the likelihood of acceptance of most of the six individual complaint procedures under observation. I also find evidence that this effect is exacerbated if states are more likely to actually bear the costs of implementation. Findings indicate that the omission of further commitment can be a negative spillover of the treaty bodies' quasi-judicial output.
Keywords: 320; UN treaty bodies; Human rights; Individual complaints; Commitment; Compliance; Costs; Bayesian learning